(untitled) (Bangladesh Journal of Botany, 2020)
Drought stress caused the decrease of pigment contents - chlorophyll a, chlorophyll b, chlorophyll a/b ratio, total chlorophyll content and carotenoids content of leaves of five rice varieties (var. BRRI Dhan-30, BRRI Dhan-32, BRRI Dhan-34, BRRI Dhan-38 and BRRI Dhan-56). Among five rice varieties, BRRI Dhan- 56 showed the least decrease of pigment content under stress. It caused the decrease of protein content of leaves of five rice varieties whereas BRRI Dhan-56 showed the least decrease (3.64%) of protein content under stress. On the other hand, drought stress increased CAT and SOD activities in the leaf of five varieties of rice and BRRI Dhan-56 showed the highest increase of CAT (37.67%) and SOD (94.17%) activity under stress. It may be assumed that higher antioxidant enzymes activities (CAT and SOD) and less reduction of protein content were related to the mechanisms of drought tolerance in rice. It is indicated that BRRI Dhan- 56 may be drought tolerant while BRRI Dhan-30, BRRI Dhan-32, BRRI Dhan-34 and BRRI Dhan-38 were drought sensitive rice varieties. Drought tolerant rice variety is selected based on pigment content, protein content and antioxidant enzymes activities (CAT and SOD).